Persepsi Masyarakat Kalianak Timur Surabaya Terhadap Tayangan Program Acara Karma (Reality Show) Di ANTV (Faculty of Communications Science, Dr. Soetomo University, 2019)
This study aims to find out how the perception of KARMA impression on ANTV by the people of east Kalianak Surabaya.the initial problems in television show, especially the KARMA reality progam which occupied the first slot of each show. Every KARMA broadcast tell about phenomena that occur in society. Strory themes such as sexual harassement, crime, and mystical things become a culture that is loved by the wider community.by using descriptive qualitative research to learn about community problem and find out the perception of KARMA.impresion as research material.the result of the study found that the KARMA show was very well liked by the people of east Kalianak Surabaya. This is due to several important element that is the center of public attention, namely the theme, story content, location conditions, studio, telent, resource. Persons and progam guides, ANTV big name and the progam show at curfew. KARMA reality show focus on element for the community and the audience.Keywords: Mass communication, reality show, perception.